Tinjauan Yuridis Terhadap Perlindungan Hak Anak Sebagai Pelaku Tindak Pidana dalam Proses Penyidikan (LEGAL DIALOGICA, 2025)
This study aims to: (1) Identify and analyze legal regulations related to the protection of children's rights as criminal offenders during the investigation process. (2) Analyze and evaluate the adequacy of regulations for the protection of children as criminal offenders during the investigation stage.This study uses a normative research method that focuses on the norms, rules, legal principles, and legal materials existing within the legal system. Normative research aims to explore and analyze legal provisions governing the protection of children's rights as criminal offenders.The results of this study indicate that the protection of children's rights as criminal offenders during the investigation stage is regulated by the Juvenile Justice and Child Protection Law (UU SPPA) and regulations related to the principles of diversion, restorative justice, and identity confidentiality. However, there are still gaps and obstacles in implementation that risk causing trauma and stigmatization, contrary to the best interests of children.The research recommends the need for clear implementing regulations to address gaps in the Child Protection and Child Protection Law, strengthen the role of Community Guidance Officers, and safeguard the confidentiality of children's identities. Regulatory harmonization, increased capacity of authorities, strict oversight, and firm sanctions for violations of children's identity are crucial for the protection and development of children in accordance with the principle of the child's best interests.AbstractPenelitian ini bertujuan untuk: (1) Mengetahui dan menganalisis pengaturan hukum terkait perlindungan hak anak sebagai pelaku tindak pidana dalam proses penyidikan. (2) menganalisis dan mengevaluasi kecukupan pengaturan perlindungan anak sebagai pelaku tindak pidana pada tahap penyidikan.Penelitian ini menggunakan metode penelitian normatif yang berfokus pada norma, aturan, prinsip hukum dan bahan hukum yang ada dalam sistem Hukum. penelitian normatif bertujuan untuk mengeksplorasi dan menganalisis ketentuan Hukum yang mengatur perlindungan hak anak pelaku tindak pidana.Hasil penelitian ini menunjukkan bahwa Perlindungan hak anak pelaku tindak pidana di tahap penyidikan diatur oleh UU SPPA dan peraturan terkait dengan prinsip diversi, keadilan restoratif, dan kerahasiaan identitas. Namun, masih ada kekosongan dan kendala pelaksanaan yang berisiko menimbulkan trauma dan stigmatisasi, bertentangan dengan kepentingan terbaik anak.Rekomendasi penelitian yaitu diperlukan peraturan pelaksana yang jelas untuk menutup kekosongan UU SPPA, memperkuat peran Pembimbing Kemasyarakatan, dan menjaga kerahasiaan identitas anak. Harmonisasi regulasi, peningkatan kapasitas aparat, pengawasan ketat, serta sanksi tegas terhadap pelanggaran identitas anak penting demi perlindungan dan pembinaan anak sesuai prinsip kepentingan terbaik anak.